Socialization of Risk Management Implementation in Improving Village Financial Management - Oktarini Khamilah Siregar; Vina Arnita; Mohd. Abidzar Bin Zainol Abidin (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
Village financial management is a crucial aspect of village governance that requires transparency, accountability, and adherence to applicable regulations. The risk of financial irregularities in village fund management remains a significant challenge faced by many village governments in Indonesia, including Klambir V Kebun Village, Deli Serdang Regency. This community service activity aimed to enhance the understanding of village apparatus regarding the implementation of public risk management in improving village financial management. The activity was conducted on November 26, 2024, using socialization and counseling methods through lectures, discussion, and question-and-answer sessions, with the distribution of modules to 10 village apparatus participants. Pre- and post-activity evaluations indicated a significant improvement in participants' understanding of risk management concepts, particularly in the areas of risk identification, risk analysis, and risk mitigation strategies. The results demonstrate that socialization of risk management is effective in improving the capability of village officials in managing village finances transparently and accountably. These findings underscore the importance of ongoing capacity-building programs for village apparatus as part of efforts to strengthen village governance and financial accountability in Indonesia.